PHYSIOLOGICAL, HAEMATOLOGICAL AND SEROLOGICAL RESPONSES IN WAD GOATS FED BROWSES WITH GLIRICIDIA HAY BASED DIETS IN DRY SEASON - Ogungbesan, A.M.; Fasina, O.E.; Olaleye, A.O.; Eniolorubda, O.O.; Adeyanju S.A.; Awojobi, H.A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
This experiment was conducted to determine the effects of Leucaena leucocephala (Lam) (Fli), Gliricidia sepium Jacq (FGs), Gmelina arborea Roxb (FGa),and Pennisetum purpureum (Schumach) (FPp), l ) and Gliricidia sepium (HGs) hay basal diet and Concentrate(Cc.) on the physiological, hematology and serum biochemistry values of WAD goats .Sixteen goats comprising 8 bucks and 8 does aged 4-6months and averaging 4.43kg in weight were divided into 4 treatments groups of 4 animals per group and each group randomly assigned to one of the 4 treatments( T1=FP-HG,T2=FG-HG,T3=FL-HG,and T4=FGa-HG) (for 12 Twelve weeks ) in a Completely Randomized Design. At the end of the trial the physiological parameters monitored are Pulse rates (bpm), Body temperature (OC), Rectal temperature (OC), .Respiratory rate(bpm), and Heat stress index with ranges within the normal reference values of 60-150, 37-40,37-42,20-40 and less than threshold of 65-72 respectively.Furtthermore, haematology parameters measured viz were, Leucogram and its differential count, Erythrogam and its derivatives and some Serum biochemical parameters. All indices of the aforementioned were all within the normal range values though a limit is from different authors which is scientifically tenable. this development presupposes that Grass- legume-concentrate (T1) and Browses Legume -legume concentrate (T 2 and T 3) as well as non-legume browse-legume browse-concentrate (T4) mixture can be sustainably subsisted and survived upon by goats depending upon their availability especially in the dry season.